School-based Factors Contributing to Students’ Indiscipline Behavior at Public Schools - Yusufu Kamara; Burhanuddin Burhanuddin; Asep Sunandar; Wusu Kargbo (International Research-Based Education Journal, 2024)
This research investigates the School-based factors contributing to students' indiscipline behavior at public schools. The researcher uses a qualitative research approach method. Therefore, the method involves synthesizing existing literature related to this topic. The article delves into the complexity of indiscipline, identifying school-based factors which include School Leadership, and Administration, Curriculum, and Teaching Methods, Poor Teachers Students Relationship, Overcrowded Classroom, School Climate and Culture, Curriculum and Teaching Methods Limited Parental Involvement as causes that disrupt a conducive learning environment. Indiscipline encompasses actions deviating from accepted standards, leading to disorder and misconduct in various settings, especially public schools.  In educational settings, it involves students disregarding rules, disruptive behavior, and violating codes of conduct. Indiscipline poses challenges to education systems and student development. The study identifies school-based factors which include crowded classrooms, lack of effective school leadership, lack of motivation, and many more as the most problematic school-based factors that influence students' indiscipline behavior at public schools. The article emphasizes the ongoing need for efforts from educational stakeholders to improve the situation.